O ensino de ciências nos anos iniciais: sinalizando possibilidades de mudanças - Goldschmidt, Andréa Inês (2012)
This current study s general idea was to investigate what students from the first years of school were aware regarding Science and if such conceptions could differ among teachers and students. After, it was intended to develop pedagogical proposals to teach Science specially to these first years of school. They were meant to serve as models to create challenges in different subjects related to Science, with attractive activities, which would take the students and teachers to understand and assimilate Science topics, turning it into a Significant Learning Process through their pre-concepts. This thesis is presented as six articles, which focus three distinct areas connected to the investigation. The first two articles present a study about Science concepts and more properly the image of a scientist among first years students and graduate students. As a follow-up, a second article debates lice infestations taking into account the school community ideas about the issue. During the research, another target was aimed, which was to develop and propose methodological activities potentially significant. The third and fourth article bring such results, with tested activities and results obtained from first years pupils. Finally, the fifth and sixth article present activities and results acquired from graduate students. To conclude and integrate these articles, considerations and suggestions were made to help change the teaching of Science in the early years of school.